PENERAPAN NORMA HUKUM PERDAGANGAN ANAK DALAM PUTUSAN PENGADILAN NEGERI MEDAN - Juliyani Juliyani; Suhaidi Suhaidi; Tan Kamello; Marlina Marlina (Universitas Sumatera Utara, 2016)
ABSTRACT Children are very vulnerable to be traded. Human trafficking in children is done in organized and non-organized crime, either domestically or internationally. They become absent of freedom and it is not uncommon that they are treated unjustly; they are even enslaved! Therefore, it is necessary to study the regulations on child trafficking, viewed from child protection in the implementation of Law No. 23/2002 on Child Protection and about judge’s attitude in handing down a verdict on the case of child trafficking in the Medan District Court. Keywords: System Implementation, Child and Human Trafficking, District Court’s Verdict